Penggunaan Alat Peraga Sistem Eskresi Siswa Kelas 4 di Mi Al- Barokah An-Nur - Siti Amanda; Muhammad Suwignyo Prayogo; Aprilia Yuliantika; Nayla Kholida (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The purpose of this study is to examine how fourth-grade students at MI Al Barokah An Nur Jember use teaching aids to learn about the excretory system. A qualitative descriptive method was used, with data collected through observation, interviews, and documentation. The results of the study show that teaching aids are crucial in helping students understand the components of the excretory system in more detail. The tools used include replicas of human excretory organs, such as the kidneys and lungs. Teaching aids serve as visual media used by teachers to attract students' attention and enhance their engagement in the learning process. They also stimulate students' motivation to learn and assist them in retaining the concepts being taught. Therefore, teaching aids have proven to be beneficial in supporting science learning in the fourth grade at MI Al Barokah An Nur Jember.